2016
DOI: 10.4103/0970-9290.186246
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of interns and postgraduate dental student's knowledge regarding equipment ergonomics

Abstract: Comprehensive understanding and practical application of EE among the participants was found to be lacking. The importance of microbreaks and chair side exercises should be emphasized and training should be initiated at an early stage before improper postural habits develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…In this study all but 2 participants were of the opinion that ergonomics should be included in the curriculum of dental students. This is in accordance with a study conducted by Rajeshwari et al, [13] students and 90 % of the interns shared the same opinion as the results of our study. This is probably due to fact that a significant number of dentist's in their lifetime experience musculoskeletal disorders or pain associated with their work.…”
Section: Discussionsupporting
confidence: 94%
“…In this study all but 2 participants were of the opinion that ergonomics should be included in the curriculum of dental students. This is in accordance with a study conducted by Rajeshwari et al, [13] students and 90 % of the interns shared the same opinion as the results of our study. This is probably due to fact that a significant number of dentist's in their lifetime experience musculoskeletal disorders or pain associated with their work.…”
Section: Discussionsupporting
confidence: 94%
“…It was observed that 76.88% of the dental practitioners had an angulation of 90 of their knee to the floor (Table 4). S Raja Rajeswari et al states 32.35% of the subjects admitted that they were unaware of desired positioning of operator's knees to hips during stool adjustment (Rajeswari SR et al 2016).…”
Section: Breaks Between Successive Patients (2-3 Minutes) 3 Breaks mentioning
confidence: 99%